Two-Level Distributed Demand-Side Management Using the Smart Energy Hub Concept. (February 2019) - Sobhani, Seyed Omid; Sheykhha, Siamak; Azimi, Mohammad Reza; Madlener, Reinhard
Abstract: Demand-side management (DSM) and the integration of the energy hub concept as a main part of future energy networks play an essential role in the process of improving the efficiency and reliability of the power grids. In this paper, we consider a smart multi-carrier energy system in which users are equipped with energy storage and conversion devices (i.e., an energy hub). Users intend to reduce their energy payment by shifting energy consumption to off-peak hours and switching between different energy carriers. This system enables both users with shiftable loads and must-run loads to be active in a DSM program. We apply game theory to formulate the energy consumption and conversion for a distributed design. In this game, players employ their strategies to schedule energy consumption for appliances and conversion devices. We propose a novel algorithm which allows to solve this optimization problem which includes heat and electricity storage devices and multiple energy carriers for a system of interconnected hubs. The results show that using the proposed algorithm based on non-cooperative game formulation to connect a Smart Energy Hub (SEH) to a network can improve the performance of the whole network by reducing the peak-to-average ratio. Furthermore, users with and must-run loads can participate in this program by both switching between the electric and natural gas network and using storage devices.